2021
DOI: 10.1038/s41598-021-82114-6
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of HPV in pterygium with no evidence of autoinoculation and the role of cytokines in pterygium with dry eye

Abstract: This study evaluated human papillomavirus’s (HPV) role in pterygium pathogenesis, its autoinoculation from genitalia to ocular surface, potential cytokines involved, and crosstalk cytokines between pterygium and dry eye (DE). This cross-sectional study enrolled 25 healthy controls (HCs) and 116 pterygium patients. Four subgroups of pterygium and DE were used in cytokine evaluations. Conjunctival and pterygium swabs and first-void urine samples (i.e., genitalia samples) were collected for HPV DNA detection usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The latter confirms our previous results and strengthens our hypothesis that interindividual variability could play an important role, as the VEGF levels are considered elevated with respect to patient-specific healthy values [ 24 ]. On the contrary, Uthaithammarat et al, did demonstrate higher VEGF concentrations in pterygium patients compared to the healthy control group [ 44 ]. Although the exact players and their corresponding contributions still need to be defined and/or further refined, it is important to note that there is a difference in the organization of the vascular network when it belongs to pterygium or a malignant transformed lesion.…”
Section: Uv-induced Damagementioning
confidence: 99%
“…The latter confirms our previous results and strengthens our hypothesis that interindividual variability could play an important role, as the VEGF levels are considered elevated with respect to patient-specific healthy values [ 24 ]. On the contrary, Uthaithammarat et al, did demonstrate higher VEGF concentrations in pterygium patients compared to the healthy control group [ 44 ]. Although the exact players and their corresponding contributions still need to be defined and/or further refined, it is important to note that there is a difference in the organization of the vascular network when it belongs to pterygium or a malignant transformed lesion.…”
Section: Uv-induced Damagementioning
confidence: 99%
“…The pathogenesis of pterygium is not completely understood, however there are the inflammatory and tumoral theories, which would be controlled by the action of the sesquiterpenes. As it was already demonstrated that inflammatory cytokines, including IL-6, IL-8, and vascular endothelial growth factor (VEGF) are elevated in the tears of the patients with pterygium [16][17] the present study investigated the effects of the sesquiterpenes β-caryophyllene and α-humulene (chemical structures in Figure 1A and 1B) on the production of inflammatory cytokines by pterygium fibroblasts, in order to determine if they can be used in the adjuvant treatment of pterygium.…”
mentioning
confidence: 99%
“…In the current study, all of the examined patients demonstrated no history of HPV infection. Concerning the involvement of HPV and other persistent viral infections, including Epstein Barr, in pterygia pathogenesis there are controversial experimental and epidemiological results (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%